Enduring colonialism : classical presences and modern absences in Indian philosophy - Raghuramaraju, A. (New Delhi : Oxford University Press, 2012)
Chiefly on Desire and liberation by Vaddera Chandidas, b. 1938.
Articles; some previously published.
Keywords: REALITY; METAPHYSICS; PHILOSOPHY, INDIC